Effects on Seidel energy of two special types of graphs by perturbing edges (Kuwait Journal of Science)
Let G be a simple undirected graph, and let S(G) be its Seidel matrix. The Seidel energy of G is defined as ES(G)=∑i=1n|λS(G)|, where λS(G),λS(G),…,λS(G) are Seidel eigenvalues of G. Recently, researchers have studied the effect of embedded edges on the distance energy of complete bipartite graphs. In this paper, the effect of perturbed edges on the Seidel energy of complete bipartite graphs and complete split graphs is studied. Finally, these graphs are ordered according to their Seidal energies. © 2024 The Author(s)